Community voices to support smoke free regulation advocacy - Dianita Sugiyo; James Henshall (Universitas Aisyiyah Yogyakarta, 2020)
The Smoke Free Regulation is a form of public regulation which indeed is needed in protecting the general community from the danger of smoking impacts. Currently, Indonesia was among those country which not ratifying the Framework Convention on Tobacco Control (FCTC), affecting on the less public advocacy regulating in people protection from tobacco smoke. The research was aimed to gain a public voices on regulation advocacy, specifically on smoke free regulation in Greater Yogyakarta. Involving 251 respondents reside in the same province, chosen through a random sampling technique. The result has been revealed a strong support for the importance of enacting such regulation to protect people from smoking. Thus, it is suggested that that the local stake holders could accommodate and following up these people voices.